Penerapan Media Digital Taxonomy Quest Meningkatkan Kognitif dan Berpikir Kritis Siswa SMP Klasifikasi Makhluk Hidup - Putri Sekar Melati; Parlindungan Sinaga (Universitas Sebelas Maret, 2025)
This study aims to analyze the impact of implementing the digital media Taxonomy Quest in improving the cognitive abilities and critical thinking skills of junior high school students on the topic of classification of living things and taxonomy. The method used is a quasi-experiment with a pre-test post-test control group design, involving two seventh-grade classes as samples. The research instruments consisted of objective multiple-choice tests based on Bloom’s taxonomy, and data analysis was conducted using the N-Gain test and t-test. The results showed that the experimental group using Taxonomy Quest experienced a more significant increase from pre-test to post-test scores compared to the control group, although the t-test results indicated the difference was not statistically significant. Factors such as interactivity, gamification, and the flexibility of digital media contributed to the improvement of students’ critical thinking skills. This study recommends the integration of innovative digital media in science learning to support the development of 21st-century skills.Thus, Taxonomy Quest has the potential to be an effective strategy for improving the quality of learning and students’ critical thinking skills in the topic of classification of living things and taxonomy.